Analysis of Environmental Literacy Readiness of Pre-service and Science Teachers in Facing Ecological and Sustainability Challenges - M. Syahruddin Amin; Donna Boedi Maritasari (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the level of environmental literacy readiness of pre-service and science teachers in East Lombok in facing ecological and sustainability challenges. This descriptive quantitative research involved 39 pre-service and science teachers in East Lombok Regency at the end of 2022. Data were collected using a questionnaire that includes 3 components of environmental literacy by adapting the criteria from NEEF. The results found that the overall score of environmental literacy of pre-service and science teachers was 143.70 and included in the high category. Detailed achievements of environmental literacy of pre-service and science teachers are: aspects of attitudes towards the environment with scores of 45.40 (high) and 45.90 (high) respectively, aspects of attention to the environment score at a moderate level with scores of 37 and 37.10. and the score of aspects of perception of the environment and its protection efforts reached 61.10 (high) and 60.90 (high). Referring to the research findings, it can be concluded that the level of readiness of pre-service and science teachers in East Lombok Regency to face ecological and sustainability challenges is at a high level